1999
DOI: 10.1023/a:1005597306671
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A novel actin binding protein has been isolated from chicken gizzard muscle. When isolated, a pair of proteins with apparent molecular weights of 79 kDa and 103 kDa are obtained; both proteins have a pI near 9.3. Peptide mapping indicates that these proteins are related. Antibodies against this protein cross-reacted with proteins from other smooth muscle containing tissues as well as skeletal and heart muscle. Traces of cross-reactive material were also detected in brain and kidney tissue. The affinity of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 18 publications
2
39
0
Order By: Relevance
“…None of these clones selfactivated in the absence of the actinin-containing pGBT9 clones, nor did they interact with a control plasmid, pVA3, containing part of murine p53 in pGBT9. Preliminary DNA sequence analysis revealed that 3c41 encoded a portion of synaptopodin, an actin-binding protein at synapses and glomerular podocytes (26), whereas 3c2 represented myopodin͞ genethonin 2, a related actin-binding protein of skeletal muscle (27). Transcript 3c8 represented a gene with no existing database entries except for ESTs.…”
Section: Identification and Cloning Of A Gene For A Skeletal Muscle ␣mentioning
confidence: 99%
“…None of these clones selfactivated in the absence of the actinin-containing pGBT9 clones, nor did they interact with a control plasmid, pVA3, containing part of murine p53 in pGBT9. Preliminary DNA sequence analysis revealed that 3c41 encoded a portion of synaptopodin, an actin-binding protein at synapses and glomerular podocytes (26), whereas 3c2 represented myopodin͞ genethonin 2, a related actin-binding protein of skeletal muscle (27). Transcript 3c8 represented a gene with no existing database entries except for ESTs.…”
Section: Identification and Cloning Of A Gene For A Skeletal Muscle ␣mentioning
confidence: 99%
“…Fesselin was purified from turkey gizzards using the method of Leinweber et al (1). The fesselin concentration was determined by the Lowry assay using bovine serum albumin as a standard.…”
Section: Protein Preparationsmentioning
confidence: 99%
“…The synaptopodin family (2) consists of proline-rich basic proteins that bind to actin (3), (4, 5). Three members of the synaptopodin family have been identified and each has multiple splice forms (2).…”
mentioning
confidence: 99%
“…Three members of the synaptopodin family have been identified and each has multiple splice forms (2). Fesselin, or avian synaptopodin 2 (6,7) is the most readily purified form of synaptopodin family members (5, 8) and is the subject of the work described here. Fesselin consists of a mixture of two polypeptides with a molecular weight of 79 and 102 kDa.…”
mentioning
confidence: 99%
See 1 more Smart Citation